Análise de qualidade dos pontos de parada de ônibus do município de São Carlos - Pinca, Maria Eduarda Petroni (Universidade Federal de São Carlos, 2019)
The collective transportation system supports the way we live today in large urban centers. Although it is a more sustainable transportation model than car use, the number of passengers served in Brazilian cities is declining. To reverse this scenario it is necessary that the public transport system is attractive from the point of view of the user, after all its operation is different from the water or energy supply system in which the user can choose other means of transportation. Thus, the objective of this study is to evaluate the quality of bus stops by calculating the Quality Score of Buses located in the main thoroughfares of the city of São Carlos. The methodology adopted has as a central point the user's opinion about the factors that influence the quality of the bus stop such as safety, coverage, seats, lighting, information and accessibility. The user's opinion is collected through a form and reverted to weighting factors that multiply the scores assigned to each factor after a technical evaluation. As a result of the questionnaire, safety and accessibility were the factors considered as the most important by the users, while the technical evaluation pointed them as the factors of better performance. The final value of the IQPO for points in the main roads of the municipality was 2.5 corresponding to a regular condition. In addition to calculating the IQPO, this study aims to understand if users have a positive view and consider it advantageous to deploy information panels in real time at bus stops that can contribute to improve one of the quality indicators of the points system bus: information. The survey revealed that 94% of respondents can see positive aspects of their implementation and that 92% would like them to be installed.
Quality analysis of bus stops in São Carlos city
Keywords: Qualidade; Transporte público urbano; Pontos de ônibus; Acessibilidade; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::OPERACOES DE TRANSPORTES; ENGENHARIAS::ENGENHARIA DE TRANSPORTES::PLANEJAMENTO DE TRANSPORTES